1992
DOI: 10.1149/1.2069429
|View full text |Cite
|
Sign up to set email alerts
|

An Interface Enhanced Spectroscopic Ellipsometry Technique: Application to Si ‐ SiO2

Abstract: In this research we demonstrate an ellipsometry technique that is sensitive to the interfacial region between a dielectric film and substrate. Essentially, a film with substrate is immersed in a liquid that index matches to the film, thereby optically removing the film from the measurement. In addition, the use of spectroscopic and multiple angles of incidence ellipsometry provide sufficient specification of the interface parameters, which, along with the enhanced sensitivity to the interface, enables the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

1993
1993
1999
1999

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 37 publications
0
14
1
Order By: Relevance
“…We have shown that the sensitivity is increased more than tenfold using the liquid ambient. 9 In our previous research, we investigated the evolution of the SiISiO 2 interface as a function of high temperature annealing (750-10000C) by SIE 10 and used the interface model shown in Fig. 2, which is also applicable to this study.…”
Section: Abstract (Maximum 200 Words)mentioning
confidence: 99%
“…We have shown that the sensitivity is increased more than tenfold using the liquid ambient. 9 In our previous research, we investigated the evolution of the SiISiO 2 interface as a function of high temperature annealing (750-10000C) by SIE 10 and used the interface model shown in Fig. 2, which is also applicable to this study.…”
Section: Abstract (Maximum 200 Words)mentioning
confidence: 99%
“…Yakovlev et al reported on the near-interfacial properties using visible spectroscopic ellipsometry with the immersion method. 35,36 They assumed that the protrusions of silicon and the suboxide exist at the interface, and determined that the interfacial layer thickness and the volume fraction are 0.98ϩ0.34 nm and from 0.687 to 0.991, respectively, summed over oxide and suboxide. Translating their result to ours, a depolarization factor L of 0.6 using the relations aϭͱ2D/(4R) and Lϭa/(aϩ2), where the radius of protrusions, R, is 0.98 nm and the distance between protrusions D, is 4.4 nm, are obtained.…”
Section: Comparison With Other Resultsmentioning
confidence: 99%
“…The SIE data were modeled using previously developed procedures 18,19,22 and using the two film model which we already found successful for studying the evolution of the SiO 2 -Si 18 -22 interface and is shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…Using this model the SIE data on all the samples were reduced into the two model parameters L N and R and these are shown in Table I. The fitted values shown were obtained using an effective medium approximation at the 90% confidence level as previously discussed in detail, 18,19,22 and in all cases the error associated with the fits were less than Ϯ10% in thickness. A systematic increase in the N content, as is represented by L N , is seen, and a decrease of R with increasing N is also observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation